Analysis of Numeracy Literacy of Junior High School Students in AKM Questions: Learning Strategies Based on Higher Order Thinking Skills at SMP Negeri 5 Tapung Hilir - Siregar, Nurliana; Siregar, Rahmat Sapaat (Jurnal Profesi Guru Indonesia, 2025)
This study aims to analyze the numeracy literacy of junior high school students in solving the Minimum Competency Assessment (AKM) questions and examine the effectiveness of learning strategies based on Higher Order Thinking Skills (HOTS) in improving these abilities. The study was conducted at UPT SMP Negeri 5 Tapung Hilir with a mixed methods approach to 60 grade VIII students. Preliminary results showed that only 38.3% of students were able to solve medium to high category numeracy problems, with major difficulties in interpreting the context and applying mathematical reasoning. After the implementation of the HOTS strategy, the average score increased from 57.6 to 78.2, accompanied by a positive change in students' more reflective and analytical thinking patterns. These findings show that HOTS-based learning is effective in improving students' numeracy literacy, and is recommended to be systematically integrated in mathematics learning to face the challenges of competency-based national evaluation.